Прогнозирование свойств металла шва повышенной прочности - Олсон, Д.Л.; Метцбауэр, Э.; Лиу, С.; Парк, И.Д. (Автоматическая сварка, 2003)
Рассмотрены особенности фазовых превращений в низкоуглеродистых и низколегированных швах повышенной прочности. При прогнозе свойств металла швов важен учет не только химического состава их, но и скорости охлаждения (Δt₈/₅), содержания кислорода, особенностей кристаллизации, а также включений. Предложены эмпирические выражения для прогнозирования механических свойств металла швов, в том числе полученных в условиях многопроходной сварки. Обсуждается аналитический подход, позволяющий быстро выбрать состав расходуемого материала для сварки определенных сталей. With the introduction of higher strength low-carbon steels, which have properties that are based on strengthening mechanisms other than the austenitic decomposition, new predictive expressions are required. As new welding processes increase productivity, it also becomes essential to present the cooling rate, (Δt₈/₅), into predictive expressions. Furthermore, the oxygen content must be included to make these expressions useful in predicting weld metal properties. In addition to the elemental consideration, influences from solidification and second phase particles, such as inclusions, affecting the weld metal solid-state transformation reactions are discussed. Empirical expressions have been developed to predict hardness, yield and ultimate tensile strength, as well as ductility and toughness for low-carbon and low-alloy higher strength steel weld metal. The difficulty introduced by multiple pass welding on weld property predictions is recognized. Various approaches, based on either deterministic analyses with numerical calculations or experimental correlations have been attempted, and these approaches are also discussed. With the availability of new analytical approaches, such a neural net regression analysis, more rapid and compatible selection of the welding consumable composition for a specific alloy and welding thermal experience can be achieved.